PENINGKATAN KEMAMPUAN MEMBACA INTENSIF PESERTA DIDIK MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) KELAS V SDN 20 BEROK GUNUNG PANGILUN KOTA PADANG - Marliza Cahyadi; Elfia Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study was motivated by the low reading ability of fifth grade students of SDN 20 Berok Gunung Pangilun Kota Padang, difficulty understanding the content of reading, difficulty determining the main idea, and difficulty concluding the content of reading, so that it has an impact on the ability to read intensively. This study aims to describe the improvement of students' intensive reading skills using the Cooperative Integrated Reading and Composition (CIRC) Model for Class V SDN 20 Berok Gunung Pangilun Kota Padang. This type of research is a Classroom Action Research (PTK) conducted in two cycles, cycle I consists of two meetings, and cycle II consists of one meeting. Each cycle consists of planning, implementation, observation, and reflection using qualitative and quantitative approaches. The research data obtained was related to the learning outcomes using the Cooperative Integrated Reading and Composition (CIRC) model. Data collection techniques are in the form of observation, test, and non-test analysis. The subjects of this study were the class teacher as an observer or observer, the researcher as a practitioner or teacher, and class V students of SDN 20 Berok Gunung Pangilun, totaling 20 people consisting of 6 men and 14 women. The results of the study showed an increase, in cycle I starting with the results of the analysis of the preparation of a) Teaching module cycle I obtained an average of 87.5% (B) increased in cycle II to 95.8% (A). b) Implementers.